2015
DOI: 10.1108/ijqss-02-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Do corporate sustainability practices enhance organizational economic performance?

Abstract: Purpose -Corporate sustainability is a growing area of importance for organizational development. Managing sustainability practices successfully is an imperative in achieving competitive advantage. This study intends to clarify the relation between sustainability practices and financial and market performance, and also, the role of non-financial performance outputs in this relation. Methodology/Approach -Using empirical data based on a large-scale survey among organizations in five countries (i.e. Germany, Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 50 publications
9
87
0
9
Order By: Relevance
“…A similar study by Mervelskemper, Kaltofen, and Stein () found that investors in German sustainability funds do not have to sacrifice financial performance. Other studies focused on the sustainability aspect and its relationship with firm financial performance (Adegbite, Guney, Kwabi, & Tahir, ; Al Abri, Bi, Mullally, & Hodges, ; Amacha & Dastane, ; del Alonso‐Almeida, Bagur‐Femenias, Llach, & Perramon, ; Kim & Lee, ; Maletic, Maletic, Dahlgaard, Dahlgaard‐Park, & Gomišcek, ; Paun, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A similar study by Mervelskemper, Kaltofen, and Stein () found that investors in German sustainability funds do not have to sacrifice financial performance. Other studies focused on the sustainability aspect and its relationship with firm financial performance (Adegbite, Guney, Kwabi, & Tahir, ; Al Abri, Bi, Mullally, & Hodges, ; Amacha & Dastane, ; del Alonso‐Almeida, Bagur‐Femenias, Llach, & Perramon, ; Kim & Lee, ; Maletic, Maletic, Dahlgaard, Dahlgaard‐Park, & Gomišcek, ; Paun, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The firms would also have to enhance its human capital through retraining, retention and employee satisfaction. These form the social objectives (Maletic et al, 2015) under sustainability studies. Having employee commitment and skills development is one of the ingredients for successful firms.…”
Section: Defining Sustainable Growthmentioning
confidence: 99%
“…This study used existing scales from previous empirical studies (Maletič et al, 2014b;Maletič et al, 2015). Because organisational performance is recognized as a multi-dimensional concept (Chenhall and Langfield-Smith, 2007;Kaplan and Norton, 1996), this study considers a more balanced approach of measuring organisational performance in a way that includes both financial and non-financial performance measures.…”
Section: Methodsmentioning
confidence: 99%
“…This study adopts the conceptualisation of the study constructs proposed by Maletič et al (2014) and operationalization of the variables utilised in prior studies (Maletič et al, 2015). One key starting point in the debate on sustainability management is the inclusion of stakeholders and the integration of their respective demands (Seuring and Gold, 2013), which are considered by some researchers to be crucial to driving sustainability performance (e.g., Asif et al;2013;Searcy, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation